Those Who Must Not Be Remembered: The Romanian Germanophiles and Their Historiographical Posterity - Ghenghea, Mircea-Cristian (Faces of War, 2025)
In the aftermath of the Great War, following the victory of the Entente and the fulfilment of the national ideal, the former internal enemy — represented by all those who had sided with the Central Powers — was gradually erased from the Romanian public space and social memory, after initially serving as the scapegoat for almost all the misfortunes and shortcomings of those difficult years. Blamed and demonised for their opinions expressed before and after Romania’s entry into the war, the intellectuals, politicians, journalists, and business owners generally known as ‘Germanophiles’ had to suffer the consequences for having chosen the wrong side in the war. Seen and despised as traitors to national interests, these Germanophiles were condemned by both public opinion and in historical writing. This text seeks to offer an overview of how Romanian historiography is understood to have dealt with this delicate issue, which emerged in the years of the Great War and had long-lasting effects.